Prinsip Retensi Arsip Elektronik di Badan Penyelenggaraan Jaminan Sosial (BPJS) Ketenagakerjaan - Harahap, Aisyah Romauli; Mayesti, Nina (Perpustakaan dan Arsip Universitas Gadjah Mada, 2025)
This study aims to identify the application of the principle of the electronic records retention schedule to the BPJS Ketenagakerjaan records management system. This Research describes the identiﬁcation of the suitability of the application of the principle of the electronic records retention schedule at BPJS Ketenagakerjaan with the ﬁfteen principles of implementing the electronic records retention schedule by Smallwood. This research aims to identify the application of the electronic records retention schedule principle to the BPJS Ketenagakerjaan records management system. This study describes the identiﬁcation schedule at BPJS Ketenagakerjaan with the 15 principles of implementing the electronic records retention schedule by Smallwood. This research uses qualitative research with a case study approach. The method of data collection is done using interview techniques. The results of research on electronic records retention at BPJS Ketenagakerjaan based on 15 principles of Smallwood's electronic records retention schedule show that 13 principles are understood, known, and applied by the records manager, while the record manager at BPJS Ketenagakerjaan does not know the other two principles. However, this study's ﬁndings indicate diﬀerences from conditions in Indonesia, where Principle 13 becomes Principle 14 and vice versa. In Indonesia, principle 14 must ﬁrst be carried out to determine internal authority starting from the top unit to the bottom unit. Furthermore, principle 13 can be carried out to determine the functionality of the tasks and responsibilities in each unit.